Pomponazzi Contra Averroes on the Intellect*. Issue 1 (2nd January 2016) - Sellars, John
Abstract : This paper examines Pomponazzi's arguments against Averroes in his De Immortalitate Animae, focusing on the question whether thought is possible without a body. The first part of the paper will sketch the history of the problem, namely the interpretation of Aristotle's remarks about the intellect in De Anima 3.4-5, touching on Alexander, Themistius, and Averroes. The second part will focus on Pomponazzi's response to Averroes, including his use of arguments by Aquinas. It will conclude by suggesting that Pomponazzi's discussion stands as the first properly modern account of Aristotle's psychology.